Ancient Vedic Mathematics: Rare Methods of Indian Mathematics (London Journal of Research In Science: Natural and Formal, 2024)
Ancient Vedic Mathematics offers several techniques and principles that can be applied to geometry, particularly in the context of geometric constructions, measurements, and calculations. While it may not have a separate branch dedicated solely to geometry, many of its sutras (aphorisms) and methods can be used to solve geometric problems efficiently. Here are some key aspects of Vedic Mathematics about geometry:
Keywords: contradiction; Neutralization Reactions; Gases; Unbalanced Equations; dark energy.; Rotating Universe; Non-isotropic Universe; Non-homogeneous Universe; Cosmological Principle; Scale Factor a(t); Conservation of Angular Momentum Principle.